Răspuns :
Explicație pas cu pas:
1.
[tex]a) \sqrt{2} \times \sqrt{8} = \sqrt{16} = 4[/tex]
[tex]b) \sqrt{27} \times \sqrt{6} = \sqrt{162} = 9 \sqrt{2} [/tex]
[tex]c) \ \sqrt{8} \times ( - \sqrt{5} ) = - \sqrt{40} = - 2 \sqrt{10} [/tex]
[tex]d)( - \sqrt{6} ) \times ( - \sqrt{24} ) = \sqrt{144} = 12[/tex]
[tex]e) \sqrt{2} \times ( - \sqrt{6} ) \times ( - \sqrt{12} ) = \sqrt{144} = 12[/tex]
[tex]f)( - \sqrt{3} ) \times ( - \sqrt{15} ) \times ( - \sqrt{10} ) = - \sqrt{540} = - 6 \sqrt{15} [/tex]
2.
[tex]a)2 \sqrt{3} \times \sqrt{2} = 2 \sqrt{6} [/tex]
[tex]b) \sqrt{5} \times 3 \sqrt{2} = 3 \sqrt{10} [/tex]
[tex]c)( - 2 \sqrt{7} ) \times \sqrt{14} = - 14 \sqrt{2} [/tex]
[tex]d) \sqrt{6} \times ( - 4 \sqrt{3} ) = - 12 \sqrt{2} [/tex]
[tex]e)( - 3 \sqrt{3} ) \times ( - 2 \sqrt{5} ) = 6 \sqrt{15} [/tex]
[tex]f)( - 4 \sqrt{1.2} ) \times \sqrt{2.5} = - 4 \sqrt{3} [/tex]
Sper ca te am ajutat!